Philosophical & sociological foundations of education - Talawar, M. S. (Himalaya Pub. House, 2010)
PART-I PHILOSOPHICAL FOUNDATIONS OF EDUCATION Unit - 1 Philosophy of Education Unit - 2 Fields of Philosophical Inquiry and Education Unit - 3 Indian Schools of Philosophy Unit - 4 Indian Philosophers of Education Unit - 5 Western Schools of Philosophy Unit - 6 Western Philosophers of Education PART - II SOCIOLOGICAL FOUNDATIONS OF EDUCATION Unit - 7 Sociology of Education Unit - 8 Social Structure and Education Unit - 9 Social Change and Education Unit - 10 Process of' Socialization Unit - 11 Equality and Education Unit - 12 Education and Economy Unit - 13 Human Rights and Co-Existence Unit - 14 Western Educational Thought Unit - 15 Modern American and European Thought on Education Unit - 16 Indian Educational Thought Unit - 17 Recommendations of Different Committees Unit - 18 Residential Type of Education in India Index.